An implementation of primary school differentiated learning - Nurwidiawati, Desi; Dhini, Dian Andita; Patras, Yuyun Elizabeth (Jurnal Pendidikan Sekolah Dasar, 2024)
Differentiated learning is a learning model designed to accommodate individual differences among students in terms of learning styles, ability levels, interests and needs. It aims to provide appropriate and relevant learning experiences for each student, recognizing that each individual is unique and has different potentials. This research aims to provide an in-depth understanding of differentiated learning and its contribution to improving the quality of education. The research method chosen in this study is the Systematic Literature Review (SLR) method. Data collection is done by documenting articles that accommodate and review articles in the period 2019 to 2023. The articles used in this study were 30 national and international journal articles obtained from the Google Scholar directory through Publish n Perish. Based on this research, it was found that the implementation of differentiated learning by utilizing technology and information can improve the quality of education in the future.